2016
DOI: 10.2214/ajr.15.15806
|View full text |Cite
|
Sign up to set email alerts
|

JOURNAL CLUB: Value of Quantitative FDG PET/CT Volumetric Biomarkers in Recurrent Colorectal Cancer Patient Survival

Abstract: SUVmax, MTVtotal, TLGtotal, and integrated score with FDG avidity and total tumor burden provide survival information for patients with biopsy-proven recurrent colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…We investigated the value of SUVmax for the discrimination between the benign and malign conditions. Gade et al 7 found a lower mean SUVmax of 8.6, Marcus et al 26 of 7.3 in recurrent CRC when compared to our mean SUVmax of 12.7. Shamim et al 27 found a significant increase of mean SUVmax in recurrence (11.8 for recurrence versus 3.7 for benign conditions) in a study on 32 patients with CRC.…”
Section: Discussioncontrasting
confidence: 63%
“…We investigated the value of SUVmax for the discrimination between the benign and malign conditions. Gade et al 7 found a lower mean SUVmax of 8.6, Marcus et al 26 of 7.3 in recurrent CRC when compared to our mean SUVmax of 12.7. Shamim et al 27 found a significant increase of mean SUVmax in recurrence (11.8 for recurrence versus 3.7 for benign conditions) in a study on 32 patients with CRC.…”
Section: Discussioncontrasting
confidence: 63%
“… 2 found a lower mean SUVmax of 8.6, Marcus et al . 26 7.3 in recurrent CRC when compared to ours (12.7). Shamim et al .…”
Section: Discussionsupporting
confidence: 40%
“…Marcus et al . 26 declared SUVmax and TLG to be higher in patients having bad prognosis. Gade et al .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that SUVmax in CRC is associated with prognostic assessment. Marcus et al 43 said that SUVmax is higher in patients with poor prognosis in CRC. Unlike SUVs, PET/CT metabolic parameters obtained by measuring high metabolic activity areas of tumors can provide volume and metabolic information for highly metabolized tumor cells.…”
Section: Discussionmentioning
confidence: 99%